Data for Index Insurance - Mann, Bristol; Dinku, Tufa; Greatrex, Helen (World Bank, Washington, DC, 2017)
The World Bank Group’s Global Index Insurance Facility (GIIF) in partnership with its regional partners has been working with researchers and scientists to refine satellite technology for index insurance product design. The International Research Institute on Climate and Society (IRI)’s Financial Instruments Sector Team—a GIIF partner—for instance, has worked in over a dozen countries on index contracts with tens of thousands of policies purchased by farmers vulnerable to climate change. The team partners with farmers and international institutions such as the World Bank Group (WBG) to explore the potential for using index insurance in developing countries to assist emerging markets, increase productivity of small farmers, and reduce threats to crops and livelihoods from climate risk.